Comprehensive Physiology 2022
DOI: 10.1002/cphy.c210032
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Stiffness in Lung Health and Disease

Abstract: The extracellular matrix (ECM) provides structural support and imparts a wide variety of environmental cues to cells. In the past decade, a growing body of work revealed that the mechanical properties of the ECM, commonly known as matrix stiffness, regulate the fundamental cellular processes of the lung. There is growing appreciation that mechanical interplays between cells and associated ECM are essential to maintain lung homeostasis. Dysregulation of ECM-derived mechanical signaling via altered mechanosensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 438 publications
0
17
0
Order By: Relevance
“…S13). Several reports have shown that ECM stiffness can trigger abnormal integrin signalling and mitochondrial dysfunction, thereby contributing to the development of disorders such as COPD, lung fibrosis, and emphysema 11,4042 . These results are consistent with our present finding that isoDGR-modified ECM proteins promote age-linked mitochondrial dysfunction in Pcmt1 -/- mouse lung, whereas targeted antibody therapy can induce immune clearance of this damage motif and restore normal metabolic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S13). Several reports have shown that ECM stiffness can trigger abnormal integrin signalling and mitochondrial dysfunction, thereby contributing to the development of disorders such as COPD, lung fibrosis, and emphysema 11,4042 . These results are consistent with our present finding that isoDGR-modified ECM proteins promote age-linked mitochondrial dysfunction in Pcmt1 -/- mouse lung, whereas targeted antibody therapy can induce immune clearance of this damage motif and restore normal metabolic activity.…”
Section: Resultsmentioning
confidence: 99%
“…S13). Several reports have shown that ECM stiffness can trigger abnormal integrin signalling and mitochondrial dysfunction, thereby contributing to the development of disorders such as COPD, lung fibrosis, and emphysema 11,[40][41][42] .…”
Section: Isodgr Impairs Pulmonary Etc and Mitochondrial Functionsmentioning
confidence: 99%
“…The stiffness of ECM is typically reported as elastic modulus (E, also known as Young’s modulus) or shear modulus (G). Several mechanical test methods have been used to measure the ECM mechanical property, including atomic force microscopy, ultrasound elastography, magnetic resonance elastography, and fluorescent microscopy ( Guo et al, 2022 ). The accumulated evidence revealed that ECM stiffening, a symbol of tissue fibrosis, is not merely an epiphenomenon of liver fibrosis, but can actively promote dysregulation of cellular function, leading to persistent and/or progressive liver fibrosis ( Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tere is growing evidence that external mechanical factors impact the confguration of biomacromolecules, the fate of cells, and the structure of tissues [4,5]. Te extracellular matrix (ECM) is a common scafold for maintaining the homeostasis of tissues and organs [6]. It forms a complex but highly organized network and is remodeled dynamically around cells that not only provides mechanical support for the completeness and resilience of cells but also modulates cell homeostasis and signal transduction [7][8][9].…”
Section: Introductionmentioning
confidence: 99%